Fetal stomach and gallbladder in contact with the bladder wall is a common ultrasound sign of stomach‐down left congenital diaphragmatic hernia. Issue 1 (24th September 2016) - Morgan, Tara A.; Basta, Amaya; Filly, Roy A.
ABSTRACT: Purpose: The aim of this study was to identify sonographic (US) findings that can assist in prenatal diagnosis of stomach‐down left congenital diaphragmatic hernia (CDH), specifically related to positioning of the abdominal contents including the stomach, bladder, and gallbladder. Methods: All US examinations with a postnatally confirmed diagnosis of stomach‐down left CDH over a 13‐year period were retrospectively reviewed for abnormal position of the abdominal contents, including whether the fetal stomach was in contact with the urinary bladder. Normal fetuses that underwent comprehensive US surveys were similarly evaluated for comparison in a 2:1 ratio. Results: Twenty‐two fetuses with stomach‐down left CDH were identified in a cohort of 278 fetuses with left CDH. In 15/22 (68.2%) cases of stomach‐down left CDH, the bladder and stomach walls were in contact. Contact of the fetal gallbladder with the fetal bladder wall was also observed and was present even more commonly (17/22 cases [77.3%]). There was no case of either the stomach or gallbladder in contact with the bladder wall in the normal fetal cohort (n = 44). Conclusions: Recognition of the fetal stomach and/or gallbladder in contact with the bladder wall can help in the detection of stomach‐down left CDH. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :8–13, 2017